2011
DOI: 10.5045/kjh.2011.46.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron deficiency anemia in the propagation of beta thalssemia gene

Abstract: BackgroundThe diagnostic criterion for beta thalassemia trait (BTT) is elevated Hb-A2 levels. Iron deficiency anemia (IDA) reduces the synthesis of Hb-A2, resulting in reduced Hb-A2 levels, so patients with co-pathological conditions BTT with IDA, may have a normal level of Hb-A2. Many socio-economic factors like unawareness, poor diagnostic facilities, and cost of molecular diagnosis (for screening purposes) result in interpretation of these subjects as normal.MethodsVenous blood samples from 200 unmarried fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…80 When it comes to β-thalassemia carriers, many cases are overlooked or misdiagnosed as iron deficiency because both conditions are the most frequent causes of microcytic anemia. 81,82 It is established that iron overload in thalassemia major induces liver cancer, yet very limited studies exist that have analyzed the association of hemoglobinopathies and thalassemia trait with malignancy risk where iron load is not a causal factor. At present, few studies have indicated certain important associations: enhanced rates of hematologic malignancies associated with HB Lepore, 83 enhanced gastric cancer rates in thalassemia trait, 84 significantly higher rates of thalassemia trait in patients with various types of cancer, 85 and high rates of cholangiocarcinoma in association with HB E. 86 Nonetheless, no studies have previously analyzed rates of β-globin mutations in chemorefractory cancers and brain tumors.…”
Section: Hb Mutations May Results In Aberrant Hemorphin Metabolism or mentioning
confidence: 99%
“…80 When it comes to β-thalassemia carriers, many cases are overlooked or misdiagnosed as iron deficiency because both conditions are the most frequent causes of microcytic anemia. 81,82 It is established that iron overload in thalassemia major induces liver cancer, yet very limited studies exist that have analyzed the association of hemoglobinopathies and thalassemia trait with malignancy risk where iron load is not a causal factor. At present, few studies have indicated certain important associations: enhanced rates of hematologic malignancies associated with HB Lepore, 83 enhanced gastric cancer rates in thalassemia trait, 84 significantly higher rates of thalassemia trait in patients with various types of cancer, 85 and high rates of cholangiocarcinoma in association with HB E. 86 Nonetheless, no studies have previously analyzed rates of β-globin mutations in chemorefractory cancers and brain tumors.…”
Section: Hb Mutations May Results In Aberrant Hemorphin Metabolism or mentioning
confidence: 99%
“…β-thalassemia major is a fatal disease that develops only when both parents are heterozygous for the β-thalassemia gene (β-thalassemia minor) [ 9 ]. Around 5,000 new β-thalassemia patients are added every year to the existing population of Pakistan [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…To halt the propagation of the β-thalassemia gene in a homozygous state (β-thalassemia major), an extensive prevention program was initiated in Pakistan in 1994, based on increased awareness of thalassemia and improved detection rates for β-thalassemia minor, particularly with respect to prenatal diagnosis. However, despite further technical advancements, the incidence of children born with β-thalassemia major has not reduced [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IDA is the most common cause of hypochromic microcytic anemia worldwide. Iron deficiency was shown to interfere with the diagnosis of β‐thalassemia trait by reducing the level of HbA 2 to a normal level . In addition, amounts of HbE are substantially reduced when iron deficiency coexists .…”
Section: Laboratory Parametersmentioning
confidence: 99%